(untitled) (Proceedings of the International Conference on Future of Education, 2022)
Coronavirus is a highly infectious disease, caused by the new Corona virus (COVID-19) and can spread from person to person through sneezing and coughing droplets. It has signs and symptoms, similar to the common cold but is dangerous and if not reported early and managed by health workers it can cause severe illness in humans and can lead to death. The disease has affected every sector of the economy, including the education sector, as a result, the education sector has devised new methods of delivering teaching and learning in the post COVID-19 era. Therefore, the need to control the spread of the virus cannot be overemphasized. This paper uses Object Oriented Methodology to analyze, design a machine learning system, which was implemented using a python interpreter and a python Integrated Development Environment (IDE) called pycharm. The implementation uses Polynomial Regression model, which is a supervised regression based machine learning model that can be used to control the spread of the virus by predicting the number of incidence of COVID-19 infections and deaths in Nigeria. Sample data dating from 23rd December 2021 to 8th May 2022 was used, which gave a high accuracy of 93% in COVID-19 confirmed cases and 100% accuracy in death cases. They both predicted low trend of COVID-19 death cases and confirmed cases in Nigeria in the next one month. This prediction will be very useful to health and government authorities in Nigeria, which have the responsibility of controlling the spread of the virus in Nigeria. It will help them to know how to adopt the various COVID-19 protocols in Nigeria.